Psychodrama Technique Group Guidance to Develop Positive Self-Concept for Students - Munte, Rohimatun Fadilah; Arsini, Yenti (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The problem in this study is the low self-concept of students which results in students becoming less confident, often comparing themselves with others, and not being able to identify themselves. This study aims to determine the effectiveness of group guidance services by using psychodrama techniques to develop students’ positive self-concept. This study uses a quantitative experimental method with a one group pretest posttest design. The population in this study is all students of class X (ten) MAN Dairi totaling 224 students with a sample of 8 (eight) students who have a low positive self-concept taken using a purposive sampling technique using a non-test instrument in the form of a questionnaire. The data analysis used was the Wilcoxon Signed Ranks Test with the results obtained an asymp significance value. Sig (2-tailed) is smaller (<) than 0.05, which is the significance value of asymp. Sig (2-tailed) of 0.012. The results obtained from the Wilcoxon signed rank test showed that group guidance services with psychodrama techniques were effective in developing students’ positive self-concept. The novelty of the research conducted by the researcher lies in psychodrama techniques in the context of group guidance for students. Although psychodrama has been used in a variety of therapeutic settings, its application in group guidance in schools is still rarely studied, and the circumstances after the findings can be seen that positive self-concept skills in students have increased compared to before.